Tectonic setting of late Cambrian to early Ordovician meta-tuffs in Kanchanaburi Province, Western Thailand - Jatupohnkhongchai, Suwijai; Phajuy, Burapha; Salyapongse, Sirot (Thai Geoscience Journal, 2022)
Meta-tuffs are mapped as a Silurian-Devonian unit in Kanchanaburi Province, Western Thailand. These rocks were discovered and described for the first time in 1976 and mentioned in the 1:250,000 Suphanburi geologic map sheet (ND47-7). The detailed petrography and geochemistry of these rocks are still unclear and insufficient. Petrographically, the meta-tuffs can be named as a meta-quartz-K-feldspar crystal tuff and meta-lithic tuff. They are made up of pyroclasts (volcanic rock, quartz, K-feldspar, devitrified glass) and epiclasts (granitic and meta-sedimentary rocks) embedded in a very fine-grained matrix. The whole-rock composition shows enrichment in SiO2 and K2O and a strong depletion in CaO and Na2O which is related to alteration and low-grade metamorphism. The meta-tuffs are divided into two groups based on immobile element classification. Group 1 rocks can be classified as dacitic-rhyolitic rocks which belong to the calc-alkaline series. Group 2 rocks are considered to be transitional rocks. Their chondrite[1]normalized patterns of both groups display light REE enrichment with nearly flat heavy REE and a negative Eu anomaly, typical for calc-alkaline volcanic rocks. Moreover, these meta-tuffs obviously show a negative Nb-Ta anomaly in the primitive mantle immobile-normalized spider diagram suggested volcanic arc environment. Both REE patterns and spider diagrams are coincident with the tectonic discrimination diagrams, which confirm that these meta-tuffs were formed in a volcanic arc environment. The zircon U-Pb dating of the meta-tuffs yield ages of 498.4+2.40/-3.0 Ma and 482.7+3.6/-1.0 Ma. These meta-tuffs are basement of Sibumasu Terrane. They were formed during the late Cambrian-early Ordovician possibly related to the closure of a proposed Proto-Tethys ocean along the margin of Gondwana.